Dealing with the most common side effect of statins - Janczewska, Martyna; Kalicka, Maria; Piekarska, Małgorzata; Kasperski, Radosław; Kobak, Joanna; Gryta, Jakub; Iwan, Karolina; Krysa, Tomasz (Journal of Education, Health and Sport, 2023)
Statins are one of the key drugs in the treatment of cardiology patients. They lower LDL cholesterol levels, thereby reducing the risk of acute cardiovascular events. Statins are among the best studied drugs, and have been proven to be effective and safe in the treatment of dyslipidemia. Data presented in studies on the prevalence of statin intolerance (SI) varies widely, according to some studies, statin tolerance is the same as placebo, however, this is a common problem in clinical practice. The most common reported symptoms of SI include muscle pain. Patients are often afraid of starting satin treatment because of possible side effects. The appearance of myopathy in patients results in their discontinuation of therapy, which results in increased cardiovascular risk. In order to minimize the risk of SI, particularly statin-associated muscular pain (SI), a key role is played by discussion with the patient, exclusion of nocebo effects, identification of risk factors, dose modification and possible discontinuation of the drug. The purpose of this paper is to review the problem of the most common of the adverse effects of statins- myopathy, in terms of incidence, probable cause, and recommended treatment of patients.